Heart rate following short‐term beta‐blocker titration predicts all‐cause mortality in elderly chronic heart failure patients: insights from the CIBIS‐ELD trial. (16th June 2014) - Düngen, Hans‐Dirk; Musial‐Bright, Lindy; Inkrot, Simone; Apostolović, Svetlana; Edelmann, Frank; Lainščak, Mitja; Šekularac, Nikola; Störk, Stefan; Tahirovic, Elvis; Tscholl, Verena; Krackhardt, Florian; Loncar, Goran; et al.
<x xml:space="preserve">Abstract</x> Aims Beta‐blockers (BBs) improve outcomes in heart failure. Results from the Cardiac Insufficiency Bisoprolol Study in Elderly (CIBIS‐ELD) trial previously demonstrated the feasibility of heart rate, not maximum dose, as a treatment goal. In this pre‐specified analysis, we investigated the prognostic value of achieved heart rate after BB optimization on long‐term mortality. Methods and results Elderly heart failure patients from the CIBIS‐ELD trial were invited to participate in a follow‐up examination 4 years after the initial 12‐week BB up‐titration period. The relationship between all‐cause mortality, BB dose, and heart rate after titration and potentially confounding clinical variables was analysed by multivariable Cox regression. In total, 728 patients (38% women; mean age 72.9 ± 5.4 years) were included. During a mean follow‐up period of 45 ± 9 months, 134 patients (19%) died, thus accumulating 2268 patient‐years at risk. There was no significant difference in baseline heart rate for survivors and non‐survivors (P = 0.19). In models adjusting for age, sex, BB pre‐treatment, ventricular function, heart rate, and NYHA class at baseline, a heart rate increase by 10 b.p.m. following up‐titration was associated with a subsequent mortality hazard ratio of 1.19 (95% confidence interval 1.02–1.38, P = 0.023). The heart rate range with the lowest mortality and the fewest treatment‐related adverse events was 55–64 b.p.m. The achieved BB dose was not associated with mortality risk. Conclusion The heart rate after up‐titration, but not BB dose, predicted all‐cause mortality risk in elderly patients with chronic heart failure. These patients should be titrated to resting heart rates between 55 and 64 b.p.m.